O kosher fone: o impacto que as mídias e estratégias de marketing geraram nas formas de espiritualidade - Lemos, Carolina Favero de la Rosa (2016)
This project aims to discuss the impact of social media and religious marketing in a campaign over the kosher cell, developed in an ultra orthodox Jewish community in Israel. We will seek to understand how a negotiation between media and religion has changed the community's relationship with spirituality. With a specific approach, concepts of spirituality, communication, digital culture, marketing, religion and social behavior on the network will be studied. A critical analysis of dialogical relationship between media and religion, how they relate historically, to what extent the media molds the needs of religion and how the latter adapts to new technologies. As theoretical framework we chose the studies of Heidi Campbell, in which the author discusses the various interactions of religions with the media along the history